Phylogenetic position of Electrostrymon picoloro, a new high elevation hairstreak from western Colombia (Lepidoptera: Lycaenidae: Eumaeini) - Prieto, Carlos Daniel; Robbins, Robert K. (Zootaxa, 2015)
The phylogenetic position of a new high-elevation butterfly species, which we describe as Electrostrymon picoloro Prieto & Robbins, new species, is assessed. The ventral wing pattern and genitalic structures of this species are unique among Electrostrymon. This species is also unique among Electrostrymon in that it occurs, so far as is known, only in habitats above 2800 m elevation. A phylogenetic analysis places this species in Electrostrymon as the sister of a multi-species clade. The ancestors of E. picoloro appear to have colonized its high elevation habitat relatively early in the phylogenetic history of Electrostrymon, but the species then did not recolonize lower elevation habitats nor did it diversify into other extant species.